Self-Efficacy on Psychological Well-Being of Early Childhood Education Teachers - Suranto Suranto; Rini Sugiarti (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
The teacher is a key source of educational success, because if the teacher is successful in teaching, it is likely that their students will be successful. The teacher is the main actor in addition to the parents and other important elements. The purpose of this study was to determine the effect of self-efficacy on psychological well-being of paud teachers in Grobongan Regency. The method used is a quantitative research method with 271 subjects using a scale. The data analysis technique used is choreal analysis using SEM-based PLS. Test of Regression Coefficient (β) 0.19 with P-Value <0.01, R Square Value 0.77. The results of the analysis test showed that there was an influence between self-efficacy on psychological well-being of paud teachers in Grobongan Regency.